The Effect of Children's Cognitive Development on Learning in Primary Schools - Hardiansyah, Framz; Maimunah Albay, Ivon Ayunatasari; Agustini, Purnama; Fitra Pradana, Dani Rifky; Rofiqi, Moh Ainor (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the influence of children's cognitive development on learning in elementary schools through a systematic literature review approach. The research was conducted by collecting and analyzing national and international journal articles published between 2019 and 2024, focusing on the relationship between cognitive development and learning outcomes in elementary education. Using databases such as Google Scholar and Open Knowledge Maps, 958 articles were initially identified, and after a two-stage screening process, 21 articles were deemed relevant. The findings reveal that cognitive development significantly affects students’ ability to process information, think critically, and apply knowledge in problem-solving contexts. Several key factors influence cognitive development, including learning environment, quality of instruction, nutrition, and social interaction. Teachers who understand the cognitive stages of their students are better able to design effective, engaging, and developmentally appropriate learning activities. Moreover, stimulating environments and balanced nutrition support children’s brain development and learning performance. The study highlights that optimal cognitive development contributes to higher academic achievement, improved social competence, and more effective collaboration in school learning contexts. These findings underscore the need for teachers and parents to create supportive conditions that foster both cognitive and socio-emotional growth in elementary education.